Taâ€™lÄ«m al-Lugah al-â€˜Arabiyyah Li Fahm AlqurÄn ( Al-MabÄdiâ€™ wa Al-MusykilÄt) - Burhan Yusuf Habibi (Jurnal Alsinatuna, 2018)
This study aims to discuss the learning Qur’anic language and its problems at SMP Islam Al-Azhar 14 Semarang. This study uses a qualitative approach of field case study. In collecting the data, this study uses interview, observation, and document analysis methods. Research instruments are researchers and interview’s guidelines, observation and document analysis. In analyzing the data, this study uses Miles-Huberman interactive analysis consisting of data reduction, data presentation, and conclusion. The results of the study indicate that the goals of Arabic learning are the students can read Al Quran correctly, and also know the meaning and grammar contained there. Learning material consists of grammar, vocabulary, reading, and writing based on Al Quran’s text. Method that used was translation grammatical method without the use of Arabic language on learning process. As for the evaluation, it uses both objective test and subjective test for cognitive skill and observation for affective skill. Learning Arabic with the specific aim of understanding the Qur'an is inseparable from various problems, including the complicated Arabic language of the Qur’an because of the miracles inside, the difference betweenstudents’ competencesin reading as well as writing the Qur'an and their Arabic background, and lack of various methods enabling the students get bored because the teacher is able to use the memorizing method only.